Problematika Hukum Perjanjian Kerja antara Perusahaan dan Pekerja - Putra, Zulfikar; Wajdi, Farid (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study described the legal consequences of work agreements between companies and workers and problems in making and implementing work agreements. This study used a qualitative research approach with a descriptive type. Data collection techniques were observation and documentation—sources of data obtained from primary and secondary data. The data obtained were analyzed by categorizing and classifying techniques. The study results showed that the legal consequences of a work agreement between the company and the employee had implications for the content of the agreement, which had legal force so that it might be obeyed by all parties and did not conflict with the rule of law. On the other hand, problems in making and implementing work agreements, namely the clauses in the agreement were not under the laws and regulations, so there was a misperception of the company's basic wages, and there was no clarity about the protection of workers whose employment relationship was terminated unilaterally, and the lack of transparency or good faith from the company to the company. In addition, the Department of Manpower and Transmigration was related to its ability to run the company's wheels.